The Participation of Pregnant Women in Helping Fathers to Quit Smoking to Prevent Stunting through A Health Belief Model Approach in Samarinda - Maya Marinda; Nur Rohmah; Ike Anggraini Gunawan (GLOBAL HEALTH SCIENCE GROUP, 2025)
The 2018 Indonesia Basic Health Research reported that 80.5% of individuals engaged in indoor smoking. Indoor smoking poses significant health risks, notably to pregnant women and their fetuses, with one potential consequence being stunting. Pregnant women, while at risk from cigarette smoke, also play a crucial role in preventing indoor smoking to mitigate stunting risks. This study aims to explore the participation of pregnant women in supporting their partners' efforts to quit smoking, utilizing the health belief model as a framework.This was observational research with a cross-sectional design. Purposive sampling was utilized for 343 respondents, with inclusion criteria for pregnant women with smoking partners. The study applied the health belief model, examining socio-demographic factors, perceived threats (severity and susceptibility), expectations (benefits, barriers, and self-efficacy), and cues to action. Path analysis was employed for data interpretation.The findings indicate a negative significant relationship between the socio-demographic construct and perceived threats. Similarly, socio-demographic factors are significantly related to expectations in a negative manner. A positive significant relationship was observed between perceived threats and the participation of pregnant women. However, expectations did not exhibit a significant direct impact on the participation of pregnant women. Conversely, cues to action demonstrated a positively significant relationship with pregnant women's participation.